THE PRODUCTION OF URBAN SPACE: THE RIGHT TO THE CITY AND THE RIGHT TO MOBILITY - Paiva, Cristiano da Silva (REVISTA GEONORTE, 2019)
The challenge faced in this paper emerges from a deep concern with the role of urban structuring and its impact on social life, thus seeking to discuss the aspects (conversations on the plurality of alternatives) on urban mobility, the right to city, and the strength of space production discussed by several authors in geography. Geographic space, in these terms, is considered the main category of Geography through the understanding of the city as a way of life, which reveals its exclusionary and contradictory nature in the conviviality, on the one hand, of areas endowed with better infrastructure in order to guaranteeing an effective capital movement, and on the other hand, provokes a paradox, since there are still spaces lacking in the basic conditions for the resident population to obtain a decent life. While the right to the city manifests itself as the superior form of rights, as a right to freedom, access to services and goods, through displacements in the urban space. The right to participatory activity and the right to access that are embedded within the right to the city, could fully reveal the use of the urban space.